SURVEY KEPUASAN KONSUMEN TERHADAP PEMANFAATAN LAYANAN E-BANKING PADA BANK-BANK UMUM DI KOTA MEDAN - Surya Dharma Munthe; Inggrita Gusti Sari Nasution (Ekonomi dan Keuangan, 2013)
The purpose of this reseach was to determine and analyze customersatisfaction with the use of e-banking services to commercial banks in thecity of Medan. The analytical method used are descriptive analysis,Customer Satisfaction Index (CSI) and the Importance PerformanceAnalysist (IPA).Results of this study showed that the majority of customers are satisfiedwith the performance of services provided by commercial banks in the cityof Medan. It can be seen from the test results using the CustomerSatisfaction Index (CSI) which is equal to 79.20%. But on testing using the Importance Performance Analysist (IPA) serviceattributes which are still to be fixed in the Responsiveness of officers to fill the empty ATM machine, the Bank had a service hours according to theneeds of its customers, the Bank has a number of ATM and its ATMnetwork numerous and easily found, Ease of transaction through ebanking services, the Bank gives attention to customer problems in the use of E-banking services, speed and responsiveness of the network / site Ebanking services, employee skills in dealing with e-banking services,engineering officer attitude to them in carrying out their duties. Thisshould be fixed so that the customer satisfaction at Comercial bank in theMedan city can be maintained.Keywords: Consumer Satisfaction, Service, Customer Satisfaction Index (CSI), Importance Performance Analysist (IPA)